A leitura literária em programas governamentais de formação de professores alfabetizadores do início do século XXI (2001-2018): o tropeço, a trapaça e o deleite - Ramalhete, Mariana Passos (2019)
This work is part of a larger research project entitled The Portuguese Language Teaching Policy in Brazil in the 2000s, coordinated by Professor Dr. Cleonara Maria Schwartz, from the Federal University of Espírito Santo (Ufes). It analyzes the concepts of literary reading endorsed by the federal literacy teacher training programs of the early 21st century, namely: Profa (2001 to 2002), Pro-Literacy (2005, 2008 and 2010 to 2012) and Pnaic (2012 to 2018). This is categorized methodologically as a bibliographic documentary research on UNESCO´s report, Education: a treasure to discover, and examinates documents of the referred programs. It is based on the theoretical framework of Bakhtin and his Circle, especially in Bakhtin (2016; 2017) and Volóchinov (2013; 2017). It privileges the conceptual categories of dialogism, utterance and polyphony to analyze the research corpus. It ponders on the epistemological constructs of Literary Literacy and their respective developments in the work with literary reading. It defends the thesis that, when conceiving the literary reading in a reductionist and superficial way, approved by international organisms and educational public politics, the ideological, political, ethical, aesthetic, historical, cultural contexts, proper of the literary text, are silenced. Thus, the seemingly playful and harmless way in which literary reading is engendered in these programs, even if under the heading of contributing to readers’ formation, as well as rejection of illiteracy, paradoxically confirm the paleness of the refutation itself. In this way, they collaborate to further consolidate the precariousness of official government policies for the Brazilian education field.